SHAFT LATERAL AND TORSIONAL VIBRATION RESPONSES TO BLADE(S) RANDOM VIBRATION EXCITATION - Ghouti, L. (2004)
In this study, an experimental set-up for blades-shaft vibration monitoring under blade(s) random vibration excitation is used. The set-up natural frequencies and mode shapes are found using the ANSYS finite element package. The blades and shaft lateral and torsional vibration are monitored using blades strain-gages, bearing accelerometers and shaft torsional strain-gages stations. The results showed that the shaft torsional vibration measurement represents the blade(s) vibration more closely than the bearing accelerometers. In particular, the blades vibration at low frequencies corresponding to the blades bending and shaft torsional coupled modes is closely represented by the shaft torsional vibration signals. The results of this study increased the confidence in using the torsional vibration measurement for blades vibration identification and shed more light on the nature of coupling between the blade bending and shaft torsional vibration that occur at low frequencies.